Flexural impact resistance of steel beams with rectangular web openings. (June 2021) - Al-Rifaie, Ali; Al-Husainy, Alaa S.; Al-Mansoori, Tariq; Shubbar, Ali
Abstract: This paper focuses on the flexural impact behaviour of steel I-beams with rectangular web openings. Published studies on impact resistance and design requirements of perforated steel beams are limited. To shed light such a topic, detailed non-linear three-dimensional finite element models (FEMs) were developed using ABAQUS. Rigorous validation process was employed to verify the FEMs built against published experimental tests in terms of force and displacement time histories. Reasonably good agreement was obtained between the numerical results and the corresponding experimental ones. Then, the validated FEMs were exploited to investigate the flexural impact resistance of perforated steel beams with rectangular openings. The factors examined in the current study were the area, depth, number and reinforcement of web openings under different impact velocities ranged between 2.214–7 m/s to provide comprehensive understanding on the flexural impact response of steel beams perforated with rectangular openings. It was observed that increasing the number of narrow web openings negligibly effected the flexural impact resistance of steel beams. Moreover, using wide openings significantly reduced the dynamic flexural resistance of such beams. Besides, slight effect on the flexural impact resistance and mid-span deflections were obtained if the depth of openings increased. Moreover, a considerable improvement was observed by providing perforated beams by horizontal steel reinforcement particularly for those with wide openings. The perforated steel beams showed similar mode of failure by generating four plastic hinges around the edges of an opening, which is the failure mode produced for perforated beams under quasi-static loading.